Legal Certainty in Recovering State Financial Losses in Corruption Crimes - Deby Rimenda Br Ketaren; Kiki Kristanto; Rico Septian Noor (Eduvest - Journal of Universal Studies, 2026)
Corruption, as an extraordinary crime, requires extraordinary measures—especially in recovering state financial losses—which demands legal certainty. This research aims to analyze legal certainty in procedures for recovering state financial losses caused by criminal acts of corruption, focusing on the role of public prosecutors and the effectiveness of the applicable legal mechanisms. Using normative legal research methods with legislative and conceptual approaches, this study processes primary and secondary legal materials through documentation and interpretative analysis techniques. The results of the study show that although procedures for recovering state losses are regulated in the Corruption Eradication Law and its derivative regulations, legal certainty has not been fully realized due to the unclear authority of the public prosecutor or the Corruption Eradication Commission (KPK) in tracking and seizing assets, as well as weak synchronization between criminal and civil instruments. Therefore, this study recommends reformulating regulations that explicitly define the authority of law enforcement agencies, providing adequate facilities and infrastructure for the Attorney General’s Office and the KPK, and strengthening the role of the community in reporting criminal acts of corruption. These efforts are expected to create legal certainty in the recovery of state losses, increase the effectiveness of restitution, and restore public confidence in the judicial system.